THE FIRST CASE OF HUMAN GENOME EDITING: CRIMINAL LAW PERSPECTIVE - D. Sergeev (BRICS Law Journal)
This article analyzes the legal assessment of the human genome modification experiment at the pre-implantation stage conducted by a group of scientists headed by He Jiankui, professor at the Southern University of Science and Technology (SUSTech) in Shenzhen, Guangdong Province, China, by means of the CRISPR/Cas9 technology. Chinese scholars have different opinions concerning He Jiankui’s experiment, but on the whole condemn it as illegal. Though CRISPR/Cas9 has been applied for quite a long time, the legislation of most developed countries is not ready to respond. The author of the article underlines the fact that despite the consolidated opinion of scholars, there is no binding international act which would restrict human genome editing. The author relies on Chinese sources in considering the main approaches to the assessment of He Jiankui’s actions in terms of criminal law (illegal medical activity, forgery of documents or fraud). Based on the analysis of Chinese criminal law doctrine, the author offers possible models of classifying separate actions related to human genome manipulation. The following cases of human genome manipulation are considered by the author as publicly dangerous and criminally liable: (a) when the embryo genome is changed by genetic engineering technologies for the purpose of its further implantation in the situation where the child’s parents are not aware of such intervention and its possible implications; (b) when genetic therapy or any other gene transfer (transgenesis) is applied to a person who is not aware of the nature of such manipulation and the possible implications of the application of the technology.